So what!. 12 - Mooney, Bel (Egmont London, 2002)
Now that Kitty's getting older it seems that she says'so what ' to everything. Homework? So what Time to get up? Who cares But Kitty does care. She cares when not doing her homework means she makes more work for herself in the end. She cares (even though she pretends not to) when she thinks she's lost Mr Tubs, her teddy bear. She cares that her friend, Rosie, is pretending not to be upset when her parents split up. And she cares when she finds out that her friend, William, is getting bullied. In fact, Kitty cares so much that she decides to stand up to the bully all on her own, in spite of him being much bigger than her